(untitled) (Fiep Bulletin - online, 2011)
Humanizing childbirth involves the relationship between health professionals, mothers, relatives, associates, technical procedures appropriate to the physical structure and hospital equipment, as well as the change of positions and attitudes of those involved in the birth process. A hospital physical fitness is required for the laboring woman has a companion during labor to perform procedures with regard to pain relief, promotion of healthy labor and delivery and the prevention of maternal and perinatal morbidity. The health care team should provide a safe environment, and the doubts of pregnant women answered in a clear and accessible. The laboring woman should not live in a hostile, with strict routines and focus only on the interests of the service and health team, should feel in a place where you can express your feelings, anxieties and fears, safe and supported. Thus, this study aimed to identify the literature and describe the effective non-pharmacological strategies that may help in parturient pain relief during labor. This is a literature review, searching for the publications available at BIREME, in the databases LILACS and MEDLINE, from 2000 to 2007, using the keywords "labor," delivery", "relief", "pain" and "labor", "delivery", "relief ", "pain". To collect the data from the reading of selected articles which contain non-pharmacological strategies for pain relief during labor, we used a script with the following strategies: lumbosacral massage, breathing exercises, walking, relaxation, freedom of position, shower and Bobath Ball. Based on the results of these studies being based this study, we observed that the lumbosacral massage, breathing exercises, walking, relaxation, freedom of position, shower and Bobath Ball, these methods are effective in relieving pain and comfort of parturients labor.